Nature Reviews Endocrinology - Greenhill, Claire; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Research.)
Nature Reviews Endocrinology is a peer-reviewed journal for endocrinologists and affiliated healthcare professionals. The journal delivers timely interpretations of key developments in endocrinology and related areas of study. Nature Reviews Endocrinology is published monthly in print and online, and includes commissioned news, commentary and opinion pieces and comprehensive narrative reviews. Articles are subject to rigorous peer-review and/ or review by in-house editors. Topics covered include prevention, diagnosis and treatment of disorders of the endocrine system and related metabolic and nutritional disorders, including diabetes and the metabolic syndrome, male and female reproductive endocrinology, thyroid, parathyroid, pituitary and adrenal disease, neuroendocrinology, bone and mineral metabolism and other areas of clinical endocrinology.
Keywords: Medicine; Endocrinology; Medicine/Public Health, general; Endocrinology